Ekskluzywizm ewangelikalny - Kubacki, Zbigniew (Poznańskie Studia Teologiczne, 2016)
Within the Christian theology of religions one distinguishes three basic paradigms: exclusivism, inclusivism and pluralism. Pluralism considers all religions as equal ways of salvation leading to God. It denies that Jesus Christ is the unique Savior of the world. Inclusivism maintains the unicity and salvivic universality of Jesus Christ, but affirms that explicit faith in Jesus Christ is not necessary for salvation for unevangelized people. Exclusivism is the view that Jesus Christ is the only Savior of the world and that one must believe God’s special revelation that culminates in the gospel of Christ in order to be saved. Evangelical theologians principally maintain this position. Interestingly enough, on the one hand they affirm that children who die in infancy (as well as people who are mentally incompetent) are included within the circle of God’s saving grace and will be saved; on the other hand, they say that since the first coming of Christ the only way of salvation is explicit faith in him. The article is divided into three parts. The first part examines the argument of those theologians about the fate of children who die in infancy and then compares it with the teaching of the Catholic Church expressed by the International Theological Commission in its document The Hope of Salvation for Infants Who Die Without Being Baptized (2007). The second part examines the biblical and theological arguments advanced by evangelical theologians in favor of exclusivism. In the third part these arguments are discussed from the perspective of Catholic theology. For Catholics as much as for evangelicals, there is no doubt that Jesus Christ is the unique Savior of the world and that salvation has always been by grace through faith. The difference concerns the content of this saving faith. Must it have as its object an explicit knowledge of Jesus Christ, as is argued by the evangelical exclusivists?